The Arab-Muslim Development of Muhammad's Teaching From Acts of "Madness" to the Arts of Spirituality and Shura. - Nouryeh, Christopher (Lewiston : Edwin Mellen Press, 2010)
This book investigates the presuppositions, namely ethics, spirituality and psychoanalysis, of the concept of shura, and how they can be applied in the art of governmentality.
Description based upon print version of record.
Keywords: Koran -- Criticism, interpretation, etc; Koran -- Criticism, interpretation, etc. -- History; Koran as literature; Literature; Koran -- Criticism, interpretation, etc. -- History; Koran as literature; RELIGION / Islam / Koran & Sacred Writings; Electronic books